The Relationship of Estrous Character with Conception Rate in Madura Cattle - Kuswati Kuswati; Dandy Prasetyo; Aulia Puspita Anugra Yekti; Trinil Susilawati (Faculty of Animal Science, Universitas Brawijaya, 2022)
This study aimed to determine the relationship between estrous characteristics with the success of AI in Madura cattle. A total of 50 female Madura cattle were used in this research. The estrus quality was observed, including vulva temperature, vulva swelling, vulva color, cervical pH, and cervical mucus. The parameters were NRR-1, NRR-2, Pregnancy Rate, and conception rate. The results showed that Madura cattle with the quality of estrus in the uneven red vulva color category showed better results than red vulva color at NRR-1, NRR-2, CR, and PR values, 100%, 93,33%, 93,33%, and 93,33% respectively. Abundant cervical mucus showed better results than the moderate mucus on the NRR-1, NRR-2, CR, and PR values, which were 100%, 87,5%, 75%, and 75%, respectively. Then a vulva temperature of 37,0-37,9ºC showed better results than a vulva temperature >38ºC in the NRR-1, CR, and PR values, namely 92,12%, 64,71%, and 70,59. Furthermore, the pH condition of cervical mucus with a pH value of 7 showed better results than cervical mucus with a pH of 8 at NRR-1, NRR-2, CR, and PR, 94,12%, 94,12%, 70,59%, and 76,47%. In the very swollen vulva category, the results were better than slightly swollen at the NRR-1 value of 100%. This study concludes that the characteristic uneven color of the vulva, the vulva temperature is 37,0-37,9, the abundant cervical mucus, cervical pH 7, and a very swollen vulva give a high percentage of the success of AI.